A working theology: an evaluation of the popular beliefs of Roman Catholic Filipino seafarers - Smith, Graeme (Practical theology, 2021)
The article explores in detail the popular theological beliefs of Roman Catholic Filipino seafarers. It argues that they organise their beliefs and practices to ensure they enjoy God‘s protection in their dangerous work place. The keeping of religious artefacts, the practice of rituals such as signing the sign of the cross before work shifts, visiting important churches before voyages and asking priests to say mass after accidents or tragic events are all explained as means by which to guarantee God’s protection. The question is then asked whether these beliefs and practices might be called a theology. It is argued that what makes them a theology is not any critical or evaluative reflective task but instead the capacity of the theologian describing the beliefs and practices as theology to convince others that the categories utilised can and should be called theology.